If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2 = 43 Reorder the terms: -2 + 9x = 43 Solving -2 + 9x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 9x = 43 + 2 Combine like terms: -2 + 2 = 0 0 + 9x = 43 + 2 9x = 43 + 2 Combine like terms: 43 + 2 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| 16x^4+8x^3=0 | | 10/2.4=p/2.64 | | -6n+10=46 | | 3(4+3r)=18 | | -2x(x-3)+4x=-(-x+1) | | (-8a)(-3/4) | | R/10=21/7 | | -48=7(7a+7)+3(8a-8) | | 1/9x-15=5 | | -6.9b+7.2=335.64 | | 47=3x+14 | | 2u+14=32 | | -2z^2=288 | | 19x-(18-5)=27 | | 18-5y=18 | | -12+4w=4(w-3) | | 10b^2+58b-12=0 | | f(x)=x^2+4x-9 | | X(x-4)=-4x+9 | | 2x-3/4=1/4 | | 10y+40=13y+2x | | -24s(s-53)=104-5y | | 8ab-ab= | | 8m^2+27m+9=0 | | X=6R-2R-2 | | x/2-4.75=1.25 | | 3p-3=p+5 | | 21*2/3 | | -x+8=56.4 | | 4(2x+7)-(6x+3)= | | 65+13=0 | | B+2b+3b=24 |